Structural properties of Ferrite system - Ismael , Leen (Latakia University Journal -Basic Sciences Series, 2018)
The sample of the series ferrite with was prepared using the usual ceramic technique. The single phase spinel structure of the sample was confirmed by X-ray diffractometry technique. The lattice parameter a decreases with increasing concentration x due to the difference in the ionic radii of and ions. We have also studied The effect of silicon on electron hopping length, founding that the electron hopping length is increasing by addition of silicon up to x = 0.2 and gradually decreasing by adding silicon over this value.